Subjective Well-Being of Women in Their Late Adulthood - Ningtyas, Lia Kaulina Suci; Tentama, Fatwa; Situmorang, Nina Zulida (Psikopedagogia, 2019)
This study aims to determine the description of subjective well-being and the factors that influence subjective well-being in senior women. This study was conducted in Yogyakarta and Madura and included retired old women aged 60 years and above. This study uses a qualitative method with a phenomenological approach, specifically through the use of interviews and observation. Data were analyzed using content analysis. Purposive sampling was used as the sampling technique in this study. The results of this study found that the subjective well-being of late adults can be viewed from both cognitive and affective components: life satisfaction, health, productive activities, life enjoyment, and confidence. Also, researchers found adverse effects, such as feelings of loneliness, sadness, and stress. The results of other studies found that religiosity, social relations, leisure time, success, and family support are contributing factors that influence the subjective wellbeing of people in their late adulthood. The results of this study can be used as a basis for developing a gerontological counseling model to develop subjective well-being in senior women